Application of the Wasatiyyah concept to the formation of the Medina Charter - Azyati Azhani Mohd Mazuki,; Wan Kamal Mujani,; Azmi Aziz,; Ermy Azziaty Rozali, (Institut Kajian Rantau Asia Barat, 2013)
The Medina Charter is the first written charter created by Prophet Muhammad s.a.w as a system of rule or a legislative system in administering Madina. The Prophet adopted the Wasatiyyah concept or the notion of moderation in constructing the Charter or constitution, for the administration of different religions and cultures in Medina. This article will shed light on the Wasattiyah concept or approach as adopted in the formation of the formation. The methodology of this study is by studying and analyzing historical documents in order to obtain a complete understanding of the Wasatiyyah concept. The study showed that the Wasatiyyah concept Prophet Muhammad s.a.w used provided rights and justice to the people of Medina.